LIABILITY AND RESPONSIBILITY - ELENA EMILIA STEFAN (Challenges of the Knowledge Society)
The violation of a social norm establishing a rule of conduct engages the violator’s liability. Responsibility is a social phenomenon and it expresses, in its shortest definition, an act of commitment of the individual in the process of social interaction. This study aims to analyze the concepts of liability and responsibility, but also the relationship between them, starting from their common fundamentals and ending with the main differences between the two notions.